Shoot Induction in White Eggplant (Solanum melongena L. Cv. Bulat Putih) using 6-Benzylaminopurine and Kinetin - Pei Ching Foo,; Ze Hong Lee,; Chee Keong Chin,; Sreeramanan Subramaniam,; Bee Lynn Chew, (Tropical Life Sciences Research, 2018)
Solanum melongena L. commonly known as the eggplant or brinjal comes from the family of Solanaceae, sharing the same ancestor with the tomato and potato. It is an economically important crop worldwide, being well studied for its medicinal properties, nutritional values and its role as an alternative model plant. The eggplant fruit has been previously used for treatments of various diseases such as bronchitis, asthma, arthritis and diabetes as well as its nutritive properties that are beneficial to the human diet. Plant transformation studies on the eggplant have been widely done for the production of transgenic eggplants harbouring genes that are beneficial for optimal plant growth and fruit production. Shoot induction is an essential step required for the successful regeneration of transformed plant tissues and therefore is an essential pre-requisite in Agrobacterium-mediated transformation. The local eggplant cv. Bulat Putih is a local cultivar of eggplant in Malaysia with white and round fruits making it a potential model plant colour pigment accumulation studies in fruit crops. The current work aims to investigate the shoot induction potential of 6-benzylaminopurine (BAP) and Kinetin from cotyledon explants of eggplant cv. Bulat Putih. Results indicated that both BAP and Kinetin were able to induce the regeneration of callus from cotyledon explants. On the other hand, Kinetin at the concentration of 2.0 mg/L successfully induced shoots at the value of 1.50 ± 0.22 shoots per explant, whereas BAP alone did not trigger any formation of shoots. This study indicated that kinetin alone is sufficient to induce shoots in eggplant cv. Bulat Putih without the presence of BAP. Solanum melongena L. biasanya dikenali sebagai terung adalah dari famili Solanaceae, yang sama asal usulnya dengan pokok tomato dan pokok ubi kentang. Ia adalah tanaman yang penting secara ekonomi di seluruh dunia dan dikaji untuk sifat perubatannya, nilai pemakanan dan peranannya sebagai model alternatif bagi tumbuhan. Buah terung telah digunakan sejak dahulu untuk rawatan pelbagai penyakit seperti bronkitis, asma, arthritis dan kencing manis serta sifat khasiatnya yang bermanfaat kepada diet manusia. Kajian transformasi tumbuhan pada terung telah dikaji secara meluas untuk penghasilan terung transgenik yang membawa gen yang bermanfaat untuk pertumbuhan tanaman yang optimum dan pengeluaran buah yang bermutu. Penginduksian pucuk adalah langkah penting yang diperlukan untuk penjanaan semula tisu tumbuhan yang berjaya kerana ianya merupakan prasyarat penting dalam transformasi menggunakan Agrobakterium sebagai pengantara. Terung tempatan cv. Bulat Putih adalah kultivar terung tempatan di Malaysia dengan buah putih dan bulat menjadikannya satu model potensi untuk kajian pengumpulan pigmen warna tumbuhan untuk tanaman buah-buahan. Kajian ini bertujuan untuk menyiasat potensi penginduksian pucuk menggunakan 6-benzylaminopurine (BAP) dan Kinetin dari eksplan kotiledon terung cv. Bulat Putih. Keputusan menunjukkan bahawa kedua-dua BAP dan kinetin boleh menginduksikan regenerasi kalus dari eksplan kotiledon. Selain itu, kinetin pada kepekatan 2.0 mg/L berjaya menginduksikan pucuk pada nilai 1.50 ± 0.22 pucuk untuk setiap eksplan manakala BAP sahaja tidak dapat menginduksikan pucuk. Kajian ini menunjukkan bahawa Kinetin sahaja sudah mencukupi untuk menginduksi pucuk dalam terung cv. Bulat Putih tanpa kehadiran BAP.